2019
DOI: 10.3348/kjr.2018.0474
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Monoexponential, Biexponential, Stretched-Exponential, and Kurtosis Models of Diffusion-Weighted Imaging in Differentiation of Renal Solid Masses

Abstract: Objective To compare various models of diffusion-weighted imaging including monoexponential apparent diffusion coefficient (ADC), biexponential (fast diffusion coefficient [D f ], slow diffusion coefficient [D s ], and fraction of fast diffusion), stretched-exponential (distributed diffusion coefficient and anomalous exponent term [α]), and kurtosis (mean diffusivity and mean kurtosis [MK]) models in the differentiation of renal solid masses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
1
14
1
Order By: Relevance
“…However, Liu et al showed that the D * of malignant breast lesions was significantly lower than that of benign lesions 33 . In addition, other studies, including the current one, have suggested that the D * value cannot effectively distinguish between different malignant lesions 11,31 . We believe that the structural differences between different tumors may be an important reason for the above results.…”
Section: Discussioncontrasting
confidence: 44%
“…However, Liu et al showed that the D * of malignant breast lesions was significantly lower than that of benign lesions 33 . In addition, other studies, including the current one, have suggested that the D * value cannot effectively distinguish between different malignant lesions 11,31 . We believe that the structural differences between different tumors may be an important reason for the above results.…”
Section: Discussioncontrasting
confidence: 44%
“…[10][11][12] The SEM DWI has been applied to malignant tumors, such as brain, kidney, cervix, and ovary tumors. [13][14][15][16][17] Only a few studies have demonstrated that SEM DWI could be useful in assessing PCa aggressiveness and for detecting PCa. 6,9,11,12 However, few studies have reported the results following the evaluation of PCa using histogram analysis of SEM DWI.…”
mentioning
confidence: 99%
“…High-grade CCRCC were characterized by higher cellularity, more nuclear atypia, higher pleomorphism, and more vascular hyperplasia and necrosis [ 36 ], which lead to increased complexity of the intracellular microenvironment. Perfusion in high-grade CCRCC are also increased with predominant blood volume and tumor vascularization, verified by the studies performed with IVIM [ 31 , 37 ] and dynamic contrast MR [ 38 ]. MK can be a surrogate biomarker for predicting nuclear grade of CCRCC.…”
Section: Discussionmentioning
confidence: 70%
“…As patients with CRCC has better prognosis than those with CCRCC and PRCC [ 30 ], distinguishing CRCC from the other 2 common subtypes of RCC before surgery is essential for choosing an appropriate strategy and predicting the prognosis. Zhang et al [ 31 ] and Ding et al [ 28 ] found that MK value of CCRCC (0.62, 0.68, respectively) was lower than non-CCRCC (0.9, 0.88, respectively). As they all include CRCC and PRCC as one group (non-CCRCC), it could not be determined whether CRCC owed highest MK values among 3 subtypes of RCC.…”
Section: Discussionmentioning
confidence: 99%